Analisis Aktivitas Sains Jenjang PAUD: Studi Kasus tentang Topik dan Tantangan Guru di Kota Bandung dan Kabupaten Bandung - Akhmad Junaedi; Cahyani, Amelia; Prastika, Lintang Ratri (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Science learning in Early Childhood Education (ECE) serves as a crucial foundation for developing children’s critical thinking skills and curiosity. However, its implementation often encounters challenges related to topic selection, teaching methods, and limited resources. This study aims to analyze the science activities being taught, the learning resources used, and the challenges faced by ECE teachers in Bandung City and Bandung Regency. Using a multi-case study approach, the research involved classroom observations and in-depth interviews conducted in 17 ECE institutions, with data analyzed thematically. Findings indicate that the most commonly taught science topics are colors and water, delivered through simple experiments using physical materials. In contrast, complex concepts such as human anatomy and engineering are rarely addressed due to teachers' limited understanding and the lack of instructional media. Key challenges include low levels of teacher scientific literacy, inadequate facilities, and the developmental characteristics of young learners that require adaptive approaches. These findings highlight the need for practice-based teacher training, the development of innovative learning media, and multi-stakeholder collaboration to support effective science instruction. This study offers practical contributions for educators, policymakers, and researchers in designing higher-quality and more sustainable science learning strategies for early childhood education.